Sexual Harassment in Cyberspace in the Perspective of Islamic Criminal Law and National Law - Abdul Syatar; Kurniati Kurniati; Rindi Rindi; Arif Rahman Ramli (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
Sexual harassment in verbal and non-verbal forms has become increasingly prevalent globally. This study revealed cases of sexual harassment in cyberspace in accordance with National Law regulations in Indonesia on immortality, such as the Criminal Code and Law Number 4 of 2008 concerning Pornography and Law Number 13 Of 2006 on Legal Protection of Witnesses and Victims. Meanwhile, in the Islamic legal order, sexual harassment in cyberspace is seen in the discussion of the Jinayah Fiqh, classified as jarimah takzir and contains elements of abomination or insulting acts. The legal protection for victims of sexual harassment in Islamic law is in the form of imposing sanctions on perpetrators, which the government determines following the magnitude of their crime. The hope of strengthening immoral punishment has become necessary for Indonesia by considering the spirit and value embodied in Islamic criminal law.